Piperacillin- Tazobactam Induced Cutaneous Reaction: A Case Report - Inamdar, Syed Zia; Katragadda, Pradeepthi; Bijjargi, Abhishek; Kulkarni, Raghavendra Vinayakarao; Bijjargi, Pooja; Gahtad, Bhagyashree (Indian Journal of Pharmacy Practice)
Piperacillin tazobactum is an extended spectrum pencillin belonging to uriedopencillin class used in the management of polybacterial infections. A 37 year old male patient admitted to the hospital with the chief complaints of breathlessness since 8 days and cough with expectoration since 2 days. The patient was initially managed with nebulization and bronchodilator therapy with subsequent administration of Piperacillin Tazobactum (4.5 gm) antibiotic to treat underlying infection. The patient complained the development of pruritis and red color skin rashes over the back of neck after receiving first dose of Piperacillin Tazobactum, the antibiotic was stopped and supportive treatment with antihistamine and corticosteroid was provided to treat allergic reaction. The symptoms were healed and patient condition was improved on discharge. The suspected drug reaction with Piperacillin Tazobactum was found to have “probable” causal relationship through Naranjo causality assessment and pose “moderate” severity as assessed through Hartwig’s Severity scale. The report suggests close monitoring of Piperacillin-Tazobactam usage among patient population.
Keywords: Piperacillin- Tazobactum; Uriedopencillin; Pruritis; Adverse drug reaction; Naranjo causality assessment.